Catalyzing Knowledge Diffusion: A Meta-Synthesis of Intellectual Property Frameworks and FDI-Driven Technology Transfer in ASEAN Free Trade Zones - Fadlan; E Arinda Chikita (HM Publisher, 2026)
The rapid economic integration of the Association of Southeast Asian Nations (ASEAN) was historically driven by Foreign Direct Investment (FDI). However, the role of Intellectual Property (IP) frameworks in transforming foreign capital into genuine technological transfer remained heavily debated. This study quantitatively and qualitatively evaluated the impact of IP frameworks and institutional quality on FDI-driven knowledge diffusion within ASEAN Free Trade Zones (FTZs). A quantitative meta-analysis and systematic synthesis were conducted utilizing empirical data extracted from nine essential econometric studies. Reported coefficients from diverse regression models were statistically converted into Standardized Mean Differences (SMD) to allow for pooled analysis. A DerSimonian-Laird random-effects model was employed, and heterogeneity was assessed utilizing the I-squared statistic. The study selection process yielded nine foundational manuscripts. Risk of bias assessment indicated high methodological quality. The pooled meta-analysis demonstrated a statistically significant positive effect of strengthened institutional and IP frameworks on technology transfer proxies (Pooled SMD = 0.46; 95% Confidence Interval: 0.32, 0.60; p < 0.001). Significant heterogeneity was observed (I-squared = 68.4%, p < 0.01). Tabulated findings revealed that FTZs significantly boosted regional innovation indices, though actual absorption depended strictly on local absorptive capacity. In conclusion, robust IP laws and high institutional quality within FTZs strongly suggest a catalytic effect on formal knowledge diffusion. To maximize labor productivity, ASEAN member states must pair strict IP protection with active learning initiatives and dedicated technology transfer incentives.